Comparison of Oropharyngeal Microbiota from Children with Asthma and Cystic Fibrosis - Sébastien Boutin; Martin Depner; Mirjam Stahl; Simon Y. Graeber; Susanne A. Dittrich; Antje Legatzki; Erika von Mutius; Marcus Mall; Alexander H. Dalpke (Hindawi Limited, 2017)
A genuine microbiota resides in the lungs which emanates from the colonization by the oropharyngeal microbiota. Changes in the oropharyngeal microbiota might be the source of dysbiosis observed in the lower airways in patients suffering from asthma or cystic fibrosis (CF). To examine this hypothesis, we compared the throat microbiota from healthy children (n=62) and that from children with asthma (n=27) and CF (n=57) aged 6 to 12 years using 16S rRNA amplicon sequencing. Our results show high levels of similarities between healthy controls and children with asthma and CF revealing the existence of a core microbiome represented by Prevotella, Streptococcus, Neisseria, Veillonella, and Haemophilus. However, in CF, the global diversity, the bacterial load, and abundances of 53 OTUs were significantly reduced, whereas abundances of 6 OTUs representing opportunistic pathogens such as Pseudomonas, Staphylococcus, and Streptococcus were increased compared to those in healthy controls controls and asthmatics. Our data reveal a core microbiome in the throat of healthy children that persists in asthma and CF indicating shared host regulation favoring growth of commensals. Furthermore, we provide evidence for dysbiosis with a decrease in diversity and biomass associated with the presence of known pathogens consistent with impaired host defense in children with CF.